A Na+ A1AO ATP synthase with a V‐type c subunit in a mesophilic bacterium. (13th January 2020) - Litty, Dennis; Müller, Volker
Abstract : A1 AO ATP synthases with a V‐type c subunit have only been found in hyperthermophilic archaea which makes bioenergetic analyses impossible due to the instability of liposomes at high temperatures. A search for a potential archaeal A1 AO ATP synthase with a V‐type c subunit in a mesophilic organism revealed an A1 AO ATP synthase cluster in the anaerobic, acetogenic bacterium Eubacterium limosum KIST612. The enzyme was purified to apparent homogeneity from cells grown on methanol to a specific activity of 1.2 U·mg −1 with a yield of 12%. The enzyme contained subunits A, B, C, D, E, F, H, a, and c . Subunit c is predicted to be a typical V‐type c subunit with only one ion (Na + )‐binding site. Indeed, ATP hydrolysis was strictly Na + ‐dependent. N, N ′‐dicyclohexylcarbodiimide (DCCD) inhibited ATP hydrolysis, but inhibition was relieved by addition of Na + . Na + was shown directly to abolish binding of the fluorescence DCCD derivative, NCD‐4, to subunit c, demonstrating a competition of Na + and DCCD/NCD‐4 for a common binding site. After incorporation of the A1 AO ATP synthase into liposomes, ATP‐dependent primary transport of 22 Na + as well as ΔµNa + ‐driven ATP synthesis could be demonstrated. The Na + A1 AO ATP synthase from E. limosum is the first ATP synthase with a V‐type c subunit from a mesophilic organism. This will enable future bioenergetic analysis of these unique ATP synthases. Abstract : In this study, the A1 AO ATP synthase with a V‐type c subunit from the mesophilic acetogen Eubacterium limosum was purified. After incorporation of the enzyme into liposomes, ATP‐dependent primary transport of 22 Na + could be demonstrated. The ATP synthase from E. limosum is the first with a V‐type c subunit from a mesophilic organism. This will enable future bioenergetic analysis of these unique ATP synthases.